Diagnostic problems in fetal visceral heterotaxy syndrome. Sonography vs. autopsy - Niszczota, Cezary; Koleśnik, Adam; Szymkiewicz-Dangel, Joanna (Cor et Vasa (Brno), 2012)
Introduction Visceral heterotaxy syndromes (VHS) are defined as abnormalities of the determination of left-right symmetry, described as left or right atrial isomerism (LAI, RAI) . Some cases do not follow classical patterns and may cause diagnostic problems. The aim of this study is to determine whether their features can be helpful or misleading in the diagnosis of VHS. Material and methods The study was based on 6 cases diagnosed sonographically and/or in autopsy. The results of examinations were re-evaluated and compared. Results Two of 6 fetuses were diagnosed to have right atrial isomerism (RAI), 3 presented left atrial isomerism (LAI) and one case was diagnosed as VHS. Cardiovascular anomalies comprised: abnormal systemic venous connections (6/6), partial anomalous pulmonary venous drainage (PAPVD) (2/6), complete atrioventricular septal defect (cAVSD) (2/6), ventricular left-hand pattern (2/6), ventriculo-arterial discordance (1/6), tricuspid atresia (1/6), mitral atresia (1/6) and tetralogy of Fallot (ToF) (1/6). Fetuses diagnosed as LAI presented complete heart block. In 2 cases of RAI and in 3 cases of LAI isomeric anatomy of the atrial appendages was observed. None of fetuses with LAI presented “polysplenia” and none of fetuses with RAI presented “asplenia”. Lungs and main bronchi were isomeric in 3 cases of LAI and in no cases of RAI. One fetus with otocephaly presented atrial situs solitus and multiple cardiac anomalies, situs ambiguus of lungs and bronchi and situs solitus of the abdominal viscera. Conclusions There are characteristic features of left and right isomerism, and they may be present in various forms. In some cases extracardiac features of VHS can be seen only on autopsy.
Keywords: Fetal Heart; Thoracic Cavity; lidé; genetické techniky; hrudní dutina; Heart Block; Autopsy; diabetes mellitus; Atrial Function; Nuchal Translucency Measurement; srdeční blokáda; Heterotaxy Syndrome; Genetic Techniques; Humans; pitva; ultrasonografie prenatální; fetální srdce; Diabetes Mellitus; heterotaxe; echokardiografie; vrozené srdeční vady; Ultrasonography, Prenatal; měření nuchální translucence; srdce - funkce síní; Heart Defects, Congenital; Echocardiography